A numerical study on the installation configuration design of compliant vertical access riser (CVAR) in deepwater. (January 2023) - Jia, Jichuan; Gu, Jijun; Chen, Leilei; Gao, Lei; Wang, Shujiang
Abstract: In oil and gas transportation, the compliant vertical access riser (CVAR) system conducts economic and operational advantages due to its special configuration. In this paper, the static performance of the CVAR is studied by an efficient numerical method. According to the unique configuration of the CVAR, the mathematical model is established based on minimum total potential energy principle. The equilibrium equations are discretized by finite difference method and then solved by Newton-Raphson technique. The accuracy of the numerical method is verified by OrcaFlex software. Detailed parametric analysis is carried out based on practical engineering requirements. The effects of buoyancy section's configuration including buoyancy factor, buoyancy section's length and buoyancy section's location, and external environmental factors including wellhead offset distance, water depth and current velocity on installation shape and mechanical properties of the CVAR are analyzed. The research shows that the presented numerical method has good applicability and flexibility for the early installation configuration design of marine risers which have no touchdown section but only one touchdown point and are equipped with multiple buoyancy blocks subjected to forces of different directions and magnitudes, such as CVARs. Highlights: Presenting a new numerical method for the static analysis of compliant vertical access riser (CVAR) system. Analyzing the effects of the buoyancy section's configuration and external environment factors on CVAR's properties. Investigating the variation law of installation shape properties of CVAR system in deepwater. Exploring the variation law of tension at touchdown point and hang-off point of CVAR system in deepwater.